Temples, Towers, Shifting Sands: "Greater Truth" in Historical Writing - Pendery, David (History compass, 2015)
This paper states two important points, which are combined into one argument. First, I identify a notion of truth can be found in two seemingly conflicting literatures—"true" historiography and "false" historical fiction. I call this variant of truth a "greater truth," or historical "truth beyond epistemology" (Kansteiner 47). I find this truth in contrast to the typical "true truth" of history writing, that is, absolute truth, objective, antiseptic truth. I argue that such greater truth guides readers toward a much deeper and more complete understanding of history. Additionally, and related to the above, I examine an intellective and to some extent philosophical fusion of fictional and factual historical writing. I argue that fictional and non-fictional varieties of historical writing are transacting modes in a single patterning and maintain that "falsity" can complement "fact" in this negotiation. I ultimately find that traditional, dispassionate historical research complements discursive, composed imagined historical fiction. My aim is to examine the basis and a coalition of historical truth claims that do not always strictly "correspond" to "what actually happened," but rather consolidates apprehension and understanding in encompassing and elevated ways. At the highest level, my analysis shows that historical fictions can be construed as credible, newly imagined representations of the past that was experienced.